2010
DOI: 10.1002/app.30648
|View full text |Cite
|
Sign up to set email alerts
|

Bubble growth in the microcellular foaming of CO2/polypropylene solutions

Abstract: This article is concerned with bubble growth dynamics in the CO 2 /polypropylene microcellular foaming process. The effect of the melt strength on the bubble growth was thoroughly investigated in theory for the first time. The theoretical results indicate that enhanced melt strength effectively restrains the bubble growth and stabilizes the bubble oscillation. Higher melt strength leads to lower bubble growth rate, shorter growth time, and smaller ultimate bubble size. Compared to the melt strength, the viscoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Studies 22,23 indicated that cells nucleate and grow in a quite short time at the start of the foaming process. According to time-temperature equivalence principle, the elasticity may increase with increasing gel content at temperatures above T g in the dynamic process, although the modulus seems to be no difference for the samples as shown in Fig.…”
Section: Inuence Of Molding Time On Pek-c Platesmentioning
confidence: 99%
“…Studies 22,23 indicated that cells nucleate and grow in a quite short time at the start of the foaming process. According to time-temperature equivalence principle, the elasticity may increase with increasing gel content at temperatures above T g in the dynamic process, although the modulus seems to be no difference for the samples as shown in Fig.…”
Section: Inuence Of Molding Time On Pek-c Platesmentioning
confidence: 99%
“…Most of the previous experimental3–7 and theoretical8 studies on PP foaming had been performed with CO 2 and basically using a batch process. From all of these studies, several conclusions may be useful to the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Melt strength or/viscoelasticity (elongational viscosity) is one of the most important properties to evaluate foam materials. Lower melting strength could cause cell rupture and non‐uniform cell structure in the process of foaming . Elastomer generally has much higher viscoelasticity than that of plastics, which results in uniform cell structure.…”
Section: Resultsmentioning
confidence: 99%